Pengenalan Nilai Budaya Aceh Melalui KPM Syedara Serumpun di Malaysia - Mawardi, Ardi; Zuniar; Munawarah; Aziz, Aisyah Binti Abdul; Mu’adzah, Afnan; Shafly, Muhammad Fathin; Mazlan, Muhamad Fakarudin Bin; Anggreani, Indah; Miranto, Fadil; Aiyubi, Teuku Muhammad Rizal; Marzuki, Siti Fathia Shalaty; Afrida (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2024)
Aceh and Malaysia have very close historical, social, cultural and intellectual relations. This relationship between the two then continued in the modern era and formed an increasingly strong bond. The KPM Syedara Serumpun Student Service Lecture is intended to reaffirm Aceh-Malaysia (Malay) ties so that it is hoped that more productive cooperation can be achieved. KPM Syedara Serumpun's activities then produced several activity outputs which were carried out at several locations in Malaysia such as at Pondok Taufiqiyah Khairiah Al-Halimiah (Pondok Pak Ya), Sultan Abdul Halim Mu'adzam Shah International Islamic University (UniSHAMS), Pantai Murni Yan, Kampung Yan, Malaysian NPK Fertilizer Sdn. Bhd. (MNFSB) and Bujang Valley Archaeological Museum. Activities will be carried out for 18 days from November 10 2023 to November 27 2023.